Analisis dampak pengembangan karir guru terhadap kinerja dan kepuasan kerja - ainiyah, thohirotul_ ainiyah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the Impact of Teacher Career Development on Performance and. Satisfaction in educational settings. Career development, which includes training, promotion, and providing professional development opportunities, is believed to contribute significantly to improving teacher performance and their job satisfaction levels. The research method used is a library research approach to analyze the impact of teacher career development on performance and job satisfaction in educational settings. This study explores various secondary sources, including scientific journals, books, research reports, and relevant education policy documents. The results of the analysis indicate that structured career development programs, such as ongoing training, professional certification, and promotion opportunities, have a positive impact on improving teacher performance, both in pedagogical and managerial aspects. In addition, career development also plays a role in increasing job satisfaction, as seen from teachers’ positive attitudes towards their work, loyalty to the institution, and motivation to improve the quality of learning. This study emphasizes the importance of support from institutions in designing career development programs that are in accordance with teacher needs and current educational challenges.